Formação continuada para abordagem de educação ambiental nos anos finais do ensino fundamental em Jandaia-GO - Gomes, Leicimar Vigilato Naves (2024)
Environmental issues need to be discussed regularly and expanded to the reality experienced by students. Therefore, raising awareness and promoting ongoing teacher training are important, since they are responsible for addressing this issue in the school environment. This will allow for dialogue and the presentation of their ideas and difficulties related to the approach to Environmental Education (EE), resulting in a collective construction of teaching proposals. This process can mitigate the difficulties faced, making it possible for the school to work with EE regularly. In this sense, the question that guides this study is based on: How can an ongoing training course in Environmental Education, in an interactive-reflective format, help Elementary School teachers, in the final years, to work with this issue? In order to answer the question of this research, the general objective of the research was to analyze the application of the ongoing training course on EE, for teachers in the final years of Elementary School, in Jandaia-GO, developed in this research. The ongoing training course constitutes the educational product and approaches EE in an interactive-reflective bias to make the process more dynamic. The product is presented in the form of an e-book, providing resources for basic education teachers to include EE in the classroom. The resources selected for the development of the course were the following: the "Tree of Dreams", the Think-Pair-Share active methodology, educational videos and films, informative texts and discussion groups. The participants in the research were twenty-one teachers who teach at a state school in the city of Jandaia, in the state of Goiás. The research was qualitative in nature, of the applied research type, and the data collection instruments were the initial analysis questionnaire to identify prior knowledge on the subject, the research teacher's logbook and the teaching sequences developed by the participants. In the discussion of the results, aspects such as the contextualization of the teacher in teaching EE, construction of knowledge about EE and the importance of collective work, possibilities for reflection on EE in the teaching process, production of teaching sequences and evaluation of the process were addressed. The results indicated that the interactive-reflective approach of the course provided a more dynamic training, leading teachers to identify the objectives of EE and the importance and responsibility of working effectively on this theme in the school environment. The investigative bias suggested for the development of the teaching sequences was perceived as having the potential to promote environmental awareness among students. Thus, the course developed demonstrated a positive impact on teacher training, encouraging them to include EE in their teaching practices. The educational product developed is available on the website of the Postgraduate Program in Science and Mathematics Teaching (PPGECM), link to educational products, and on the EduCapes portal under the number http://educapes.capes.gov.br/handle/capes/921070.